Fracture toughness of recycled carbon fibers reinforced cement mortar and its environmental impact assessment - Tao Shi; Kun-Ming Li; Cheng-Zhe Wang; Zhe Jin; Xin-Kai Hao; Peng Sun; Yan-Xing Han; Chong-Gen Pan; Ning Fu; Hai-Bo Wang (Case Studies in Construction Materials)
This paper aims to investigate the mechanism of the effect of recycled carbon fibers on the fracture toughness of cement mortar and assess their environmental impact. The physical and interfacial properties of RCF were first characterized and found comparable to those of virgin carbon fibers (VCF). Three-point bending tests revealed that RCF significantly enhances the fracture energy, ductility index, crack initiation toughness, unstable toughness and cohesive toughness of cement mortar by up to 446.84 %, 238.71 %, 104.22 %, 137.12 % and 169.09 %, respectively. Additionally, the bilinear softening constitutive curve for recycled carbon fibers reinforced cement mortar was applied to compute the cohesive toughness which was validated by experiments and the related research on virgin carbon fibers reinforced cement mortar was conducted for comparison. Finally, a strength-based life cycle assessment showed that the global warming potential and primary energy depletion indicators of RCF-reinforced mortar were reduced by 38.47 % and 13.79 %, respectively, compared to VCF-reinforced mortar. These results confirm the engineering feasibility and sustainability of using RCF as a substitute for VCF in cement mortar.